UMA OMMATOPTERA E UMA PORPHYROMMA NOVAS DO BRASIL (Orthoptera, Tettigoniidae, Pseudophyllinae) - Piza Jr., S. de Toledo (REVISTA DE AGRICULTURA, 2020)
UMA OMMATOPTERA E UMA PORPHYROMMA NOVAS DO BRASIL (Orthoptera, Tettigoniidae, Pseudophyllinae)